Penerapan Model Problem-based learning dalam pembelajaran IPAS untuk meningaktkan hasil belajar siswa kelas IV di SDN Leomadamu - Ranga, Tresly Putry; Koro, Maxsel; Kota, Martha K (Journal of Character and ELementary Education, 2025)
The aim of this study is to improve the learning achievement of fourth-grade students at SD Negeri Leomadamu through the implementation of the problem-based learning model, which is focused on the history of the students' hometown. This research is a Classroom Action Research (CAR) conducted in several cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study are 20 fourth-grade students, comprising 9 boys and 11 girls. The data collection techniques used in this study are observation and learning outcome tests. The findings indicate that the average score of teacher activity in cycle I was 61.25, while in cycle II, it increased to 83.75, showing an improvement of 23%. The average score of student activity in cycle I was 66.25, and in cycle II, it increased to 92.5, showing an increase of 26%. The students' test results also showed improvement, with 9 students achieving the Minimum Mastery Criteria (MMC) in cycle I (45%), and 18 students achieving MMC in cycle II (90%). Based on the data analysis, it can be concluded that the implementation of Problem-Based Learning can improve students' learning outcomes on the topic of the history of their hometown in the fourth grade at SD Negeri Leomadamu.